Digital Banking Adoption: Evidence from the Nigerian Youth Market - Saygili, Ebru (International Journal of Contemporary Economics and Administrative Sciences, 2024)
This study aims to identify the factors influencing the adoption of digital banking in the Nigerian youth market. The research explores the adoption of both mobile and internet banking as part of a single digital banking concept. The research model extends the technology acceptance model (TAM) by further examining the impact of awareness, culture, social norms, perceived trust, perceived security on behavioral intention. The results suggest a strong influence of perceived trust on behavioral intention to adopt digital banking. Perceived ease of use, perceived usefulness, perceived security and perceived risk are key determinants of perceived trust in the Nigerian context. Other factors affecting behavioral intention are awareness and social norms.